Analisis Zona Selamat Sekolah Terhadap Keselamatan Penyeberang Jalan di SD Negeri 36 Sail Kota Pekanbaru - Abdul Kudus Zaini; Muchammad Zaenal Muttaqin; Muhammad Habibi (PT FORMOSA CENDEKIA GLOBAL, 2022)
Pekanbaru is the capital and largest city in Riau province. This city is one of the largest economic centers in the eastern part of Sumatra Island. Safe School Zone (ZoSS) is a location/area on a certain road segment which is a time-based speed zone to regulate vehicle speed in the school environment. The maximum permitted speed limit for entering ZoSS, especially on secondary arterial roads, is 25 km/hour and in general the speed limit for vehicles passing through ZoSS in Indonesia is generally 20-30 km/hour. The purpose of this study was to evaluate the application of the traffic safety zone at SD Negeri 36 in Pekanbaru City. This research was conducted using the Likert Scale method by distributing questionnaires asking questions about the behavior of drivers and parents. The results showed that the construction of the shoulder of the road is the most important infrastructure in supporting ZoSS in the area. In addition, the installation of speed limit signs is also a need for ZoSS which is built in the area. In the ZoSS area marking issue, the need for zebra cross markings and noise bands is an important priority in improving school area safety. This study also reviews various pedestrian safety issues in the area, such as the behavior of motorists who do not reduce their speed when crossing in front of the school, vehicle violations such as not wearing a helmet and not installing a rearview mirror. ZoSS concept.